2007
DOI: 10.1074/jbc.m700451200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Hairpin Ribozyme Active Site Architecture

Abstract: The hairpin ribozyme is a small catalytic motif found in plant satellite RNAs where it catalyzes a reversible self-cleavage reaction during processing of replication intermediates. Crystallographic studies of hairpin ribozymes have provided high resolution views of the RNA functional groups that comprise the active site and stimulated biochemical studies that probed the contributions of nucleobase functional groups to catalytic chemistry. The dramatic loss of activity that results from perturbation of active s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 43 publications
3
41
0
Order By: Relevance
“…These results are in accord with the experimental estimate of 20-21 kcal/mol (Nesbitt et al 1999;Fedor 2000;Kuzmin et al 2005). Nonetheless, this does not preclude alternate mechanisms with explicit nucleobase involvement, such as A38 and G8 acting as general acid and general base catalysts (Rupert et al 2002;Ferré-D'Amaré 2004;Cottrell et al 2007), respectively, which could further lower the barrier. In order to address the question as to what extent the electrostatic environment and nonspecific interactions alone can account for the observed rate enhancement, electrostatic solvation free energies are computed at various stationary points on the free energy surface and are compared to the values at the reactant state.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…These results are in accord with the experimental estimate of 20-21 kcal/mol (Nesbitt et al 1999;Fedor 2000;Kuzmin et al 2005). Nonetheless, this does not preclude alternate mechanisms with explicit nucleobase involvement, such as A38 and G8 acting as general acid and general base catalysts (Rupert et al 2002;Ferré-D'Amaré 2004;Cottrell et al 2007), respectively, which could further lower the barrier. In order to address the question as to what extent the electrostatic environment and nonspecific interactions alone can account for the observed rate enhancement, electrostatic solvation free energies are computed at various stationary points on the free energy surface and are compared to the values at the reactant state.…”
Section: Resultssupporting
confidence: 81%
“…The hairpin ribozyme (HPR) (Walter and Burke 1998;Lilley 1999), which catalyzes the reversible, site-specific phosphodiester bond cleavage of an RNA substrate, is unique in that the chemical steps of the reaction do not require a specific metal ion in the active site (Walter and Burke 1998;Lilley 1999;Doherty and Doudna 2001;Rupert et al 2002;Bevilacqua 2003) but is able to achieve rate acceleration similar to other metal-dependent ribozymes (Fedor 2000). There is an active debate regarding the origins of the catalytic proficiency of HPR, focusing mostly on the role of active site nucleobases in general acid and base catalysis (Hampel and Cowan 1997;Nesbitt et al 1999;Fedor 2000;Pinard et al 2001;Ryder and Strobel 2002;Kuzmin et al 2005;Cottrell et al 2007;Tang et al 2007). X-ray crystallographic structures of HPR provide valuable insight into the active site conformation in the reactant state (Rupert and Ferré-D'Amaré 2001;Salter et al 2006), transition state, and product state mimic structures (Rupert et al 2002;Torelli et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the transition state mimic structure with a pentavalent vanadate ion at the scissile phosphate position, it has been suggested that A38, in protonated form, acts as a general acid in the cleavage reaction. 4,24,25 The G8 nucleotide base has been implicated in the stabilization of the transition state. 4,25 This is consistent with the results from nucleotide analog interference mapping experiments.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 G8 and A38 are critical in catalysis: the deletion of the G8 base decreases the reaction rate by a factor of 350, and the deletion of the A38 base decreases the rate more than 10 000-fold relative to the wild-type control. 9,24,28,29 One important factor is the protonation states of the scissile phosphate and other nucleotides present in the active site and their relationship to the pH-rate profiles. Although G8, A38, and other nucleobases have been found to significantly affect the catalytic efficiency, 26,27,30,31 their specific roles in catalysis have not yet been clearly defined.…”
Section: Introductionmentioning
confidence: 99%